Damping Multimode Switching Control of Semiactive Suspension for Vibration Reduction in a Wheel Loader - Tao Wei; Liu Zhiqiang (Shock and Vibration)
The aim of this work is the control design and analysis of a semiactive axle suspension system for vibration reduction in a wheel loader. Unlike a traditional semiactive suspension system with continuously adjustable shock absorber, in this work, a novel axle suspension with multiple damping modes is proposed for the wheel loader. The multimode switching damping characteristics are achieved by just changing the discrete statuses of two high-speed switch electromagnetic valves, which makes the damping adjustment simpler and more reliable. However, because of the existence of discrete events, i.e., the on-off statuses of switch electromagnetic valves, the axle suspension proposed for the wheel loader poses a challenging hybrid control problem. To solve this problem, the mixed logical dynamical (MLD) modeling approach for hybrid systems is applied to model the dynamic characteristics of the system damping control procedure. Using this model, a hybrid model predictive control (HMPC) strategy is further designed, which can determine the optimal switching sequences of the discrete damping modes according to the axle suspension performance indices. Finally, to verify the effectiveness of the proposed semiactive axle suspension with multiple damping modes and its control approach, simulation analyses are conducted.